SOSIALISASI PELATIHAN PEMBUATAN PUPUK ORGANIK DARI LIMBAH RUMAH TANGGA KKN PMD UNRAM DESA BENETE - Pariani, Baiq Suci; Utami, Dodi; Haura, Hilmi Amalia; Puniartha, I Gede Jaya; Pratama, I Putu Yudha; Fadila, Kasturi Anisa; Azzuri, Raden Jufri; Ariani, Resa Dwi; Florensal, Salisa Amanih Hasyim; Raihanun, Siti (Universitas Mataram, 2024)
The socialization of organic fertilizer making training is a form of student contribution in overcoming problems in the Benete Village community. This activity aims to educate the public on the importance of protecting the environment and remanaging household waste into organic fertilizer in Benete Village, Maluk District, West Sumbawa Regency. The method used in this activity is observation. KKN students participated in environmental cleaning activities, counseling on the importance of maintaining cleanliness, and providing education to the people of Benete Village about the use of household waste as compost.